Tasmannia lanceolata (Poir.) A.C.Sm. Berry and Leaf Extracts Inhibit Proliferation and Induce Apoptosis in Selected Human Carcinoma Cell Lines - Shalom, Joseph; Cock, Ian Edwin (Pharmacognosy Communications)
Background: Tasmannia lanceolata berries and leaves have high antioxidant capacities and high levels of therapeutic phytochemicals. Despite this, the anticancer activity of T. lanceolata extracts has not been adequately explored. Materials and Methods: This study examined the anti-proliferative of T. lanceolata berry and leaf extracts against a panel of human carcinoma cell lines using MTS assays. The apoptotic activities were examined using cell imaging and caspase-3 activity assays. LC-MS and GC-MS headspace analysis were used to identify noteworthy phytochemical components. Results: The methanolic, aqueous and ethyl acetate extracts inhibited the proliferation of HeLa, Caco-2, Jeg-3, JAR, MC3T3-E1 and MG63 cell lines. The aqueous leaf extract was a particularly potent inhibitor of proliferation against most cell lines (HeLa IC50 = 230µg/mL; Caco-2 IC50 = 150µg/mL; Jeg-3 IC50 = 488µg/mL; JAR IC50 = 450µg/mL; MC3T3 IC50 = 195µg/mL; MG63 IC50 = 315µg/mL). The berry and leaf ethyl acetate extracts were also good inhibitors of proliferation of the same cell lines, albeit with slightly higher IC50 values. Morphological features consistent with apoptosis were evident in Caco-2 cells exposed to the berry and leaf ethyl acetate extracts, and the aqueous leaf extract. Furthermore, exposure of Caco-2 to sub-lethal concentrations of these extracts induced significantly elevated levels of caspase 3, indicating that the extracts induced apoptosis in Caco-2 cells. Conclusion: All T. lanceolata berry and leaf extracts induced apoptosis in a panel of cancer cells and were nontoxic in the ALA toxicity bioassay and in a HDF cell viability assay, supporting their potential as cancer chemotherapies.
Keywords: Winteraceae; Tasmanian pepper; Mountain pepperberry; Anti-cancer activity; Anti-proliferative activity; Antioxidant capacity; Apoptosis